Difficulties in recruiting frail older inpatients to intervention studies. Issue 4 (20th October 2015) - MacFarlane, Shauna; Charlton, Karen; Ferguson, Allison; Barlogie, Jessica; Lynch, Patricia; McDonell, Lyn; Connolly, Wendy; Barone, Lilliana; Russell, Peter; Mason, Michelle; Potter, Jan; Milosavljevic, Marianna
Abstract: Aim: To describe difficulties experienced with recruitment of frail, malnourished inpatients aged 65+ years to a 12‐week multidisciplinary home‐based nutrition and physical activity intervention (SUSTAIN) and to identify factors associated with non‐participation. Methods: A multidisciplinary team approach to recruitment involved monthly team meetings, weekly clinician case conferences and strategic planning to accommodate patient needs (provision of transport, easy access to facilities, appropriate written/verbal information). Intensive recruitment occurred in eligible inpatients from a major acute tertiary and rehabilitation hospitals in a local health district over seven months. Results: Of the 124 patients screened, 88 were not eligible, 32 declined, and 4 consented. Neither socio‐demographic nor clinical characteristics (age, gender, clinical diagnosis, birthplace, cognitive function, length of stay or nutritional status) explained non‐participation or ineligibility or refusals rates. Conclusions: The advanced age and poor overall health status of this population necessitates alternative recruitment strategies to improve participation in clinical trials and improve generalisability for clinical practice.